Genotyping and Phylogenic of Norovirus as Main Cause of Children Gastritis in Thi-Qar province - Leaby Chelab, Rahman; Kamel Al- Moussawi, Duaa; Abdul Hussain Jarullah, Basim (University of Thi-Qar Journal of Science, 2019)
Norovirus consided as the second cause of viral diarrhea in children.The current study included examination of 200 (115 females and 85 males) stool sample of diarrhea and abdominal pain suffering children, less than 5 years of age. The samples were divided into nine groups according to the age of the children: 1-2, 3-5, 6-8, 9-11, 12-17, 18-23, 24-35, 36-48, 50-55 month. Stool samples were divided for two part, the first part for the molecular diagnosis of virus by real time PCR and then gene sequences of virus and the second part used for ELISA test. Results of real time PCR test revealed that 35 positive sample out of 200 with a percentage of (17.5%).( AccuZo1TM total RNA extraction kit(Bioneer, Korea was used in this test). Real time PCR results showed that Depend on age groups the highly morbidity between 18-23 months (25.8 %) and there was significant differences between age groups on probability ≤0.05. Results showed that high percentage of infection between children depend on artificial nutrition Top value was (21.7%) and the low percentage of infection in children depend on mixed nutrition (breast milk and cereal meals) was (12.6%). ELISA test results included 25 positive samples from total of 200 samples percentage was (12.5%). The sensitivity of this test was 71.4% while specifity was 94% compare to Real time PCR. ELISA test showed that the age group (18-23 months) was (25.8%). with a significant difference at (P>0.05). Artificial feeding is higher than (15.2%) and normal feeding is lower (9.7%). From the positive samples 8 samples sent for gene sequences, four samples were revealed compatibility to GII.2, three samples to GII.4 and one sample compatible with GΙI.3. depend on base data of NCBI.